VS02.02: LAPAROSCOPIC TRANS-HIATAL REPAIR FOR BOERHAAVE'S SYNDROME: A CASE REPORT. (14th September 2018) - Masui, Hideyuki; Kobayashi, Hiroyuki; Kondo, Masato; Kaihara, Satoshi; Hosotani, Ryo
Abstract: Description: Introduction Spontaneous esophageal rupture, also known as Boerhaave's syndrome, is an uncommon and potentially life-threatening condition that requires urgent surgical management. We report a case of spontaneous esophageal rupture that was successfully treated by primary closure and drainage laparoscopically. Case report The patient was a 49 year-old man with a history of liver cirrhosis. He experienced sudden-onset epigastric pain triggered by vomiting after drinking alcohol, and transported to our hospital. On admission, a thoracic CT scanning revealed mediastinal emphysema without pleural effusion. We diagnosed BS and performed an emergency operation. We chose laparoscopic trans-hiatal approach as it was thought to be minimally invasive compared with open thoracic surgery. Five trocars were placed in a similar way of gastric cancer surgery. We identified laceration on the left wall of the lower esophagus under assistance of intra-operative upper endoscopy, and conducted drainage and repair by primary closure with continuous barbed suture. Finally, an omental pedicle flap was applied for over sutured site. The operation time was 214 minutes and the amount of blood loss was 50 cc. In the post-operative course, intra-mediastinal abscess was observed and he required antibiotic therapy. However, the patient was discharged on the 16th post-operative day without a serious complication such as anastomotic leakage. Discussion Primary esophageal repair is the gold standard in Boerhaave's syndrome and the approach is usually left thoracotomy. However, if there is no perforation into the thoracic cavity as in our case, less invasive approach should be considered such as laparoscopic trans-hiatal approach. We could observe the lower esophagus completely under a good field of view in this approach. There are several treatments, and it should always be tailored to the patient's condition. Laparoscopic trans-hiatal approach is considered to be useful for the treatment of lower esophageal wall rupture. It is difficult to conduct a comparative study of the various methods that can be used to treat spontaneous esophageal rupture in cases that require emergent surgery, as the number of cases is limited. Therefore, the further accumulation of cases is necessary. Disclosure: All authors have declared no conflicts of interest.